A Study of Writing: A Discussion of the General Principles Governing the Use and Evolution of Writing - Gelb, Ignace J. 1907-1985 (Chicago University of Chicago, 1974)
This book contains twelve chapters, but it can be broken up structurally into five parts. First, the place of writing among the various systems of human intercommunication is discussed. This is followed by four chapters devoted to the descriptive and comparative treatment of the various types of writing in the world. The sixth chapter deals with the evolution of writing from the earliest stages of picture writing to a full alphabet. The next four chapters deal with general problems, such as the future of writing and the relationship of writing to speech, art, and religion. Of the two final chapters, one contains the first attempt to establish a full terminology of writing, the other an extensive bibliography.The aim of this study was to lay a foundation for a new science of writing which might be called grammatology. While the general histories of writing treat individual writings mainly from a descriptive-historical point of view, the new science attempts to establish general principles governing the use and evolution of writing on a comparative-typological basis. The importance of this study lies in its being the first systematic presentation of the history and evolution of writing as based on these principles. Some specific results of the new reconstruction are: Elimination of the so-called word writings and their replacement by the word-syllabic type; assignment of the socalled Semitic alphabet to the syllabic type; placing the socalled Maya and Aztec writings not under writings proper but under forerunners of writing; conclusion that the mysterious Easter Island inscriptions do not represent writing but formal designs for magical purposes.
Keywords: Linguistics; Cuckoo